Decision Making and Decisional Tipping Points in Homicide Investigations: An Interview Study of British and Norwegian Detectives. Issue 2 (21st January 2013) - Fahsing, Ivar; Ask, Karl; Roach, Jason
Abstract An interview study explored criminal detectives' views of critical factors related to decision making in homicide investigations. Experienced homicide investigators in Norway (n = 15) and the UK (n = 20) were asked to identify decisional 'tipping points'—decisions that put detectives in a mindset focused on verifying the guilt of a suspect—and situational or individual factors that relate to these decisions. Two types of decisions were identified as typical and potentially critical tipping points: (1) decisions to name, arrest, or charge a suspect, and (2) decisions on main strategies and lines of inquiry in the case. Moreover, 10 individual factors (e.g. experience) and 14 situational factors (e.g. information availability) were reported as related to the likelihood of a mindset shift, most of which correspond well with findings in previous decision‐making research. The consensus between British and Norwegian detectives was very high, and the findings indicate that experienced detectives are aware of many of the risk factors and obstacles to optimal decision making that exist in criminal investigations. Copyright © 2013 John Wiley & Sons, Ltd.